Effects of fiscal credibility on inflation expectations: evidence from an emerging economy (Public Sector Economics - submission site, 2021)
This paper analyses the impact of fiscal imbalances on expectations for an emerging economy with inflation targeting. In particular, based on the Colombian experience, we build a fiscal credibility index and evaluate its impact on inflation expectations for the 2004-2019 period. To analyse fiscal and monetary interactions, we propose an econometric model and use the OLS and GMM methods. The results show that the loss of fiscal credibility, associated with divergences between the fiscal deficit and agents’ expectations, can increase inflation expectations by between 9% and 12%. Furthermore, inflation expectations in Colombia incorporate important macroeconomic information related to unemployment, GDP and exchange rates.